EFFECTS OF DIFFERENT LEVELS OF DIETARY CARBOHYDRATE ON GROWTH AND FEED UTILIZATION OF CATFISH (CLARIAS BATRACHUS L.) FRY - Mollah, M F A; Alam, M S (Indian Journal of Fisheries, 2011)
Six diets containing different levels of carbohydrate namely 0, 5,10,15,20 and 25% were tested on Qariasbatrachus fry of 0.9 to 1.14 g body weight for a period of 20 weeks. The levels of protein and lipids weremaintained at an average of 40% and 9.3% respectively for all the diets. The growth, food conversionefficiency and protein efficiency ratio were compared at the end of the experiment. The diets containing 15%and 29% carbohydrate produced significantly better growth than the diets containing 0,5,10 and 25% carbohydrate.No significant difference weight-gains was observed among the fish fed on diets containing0, 5,10 and 25% as well as between 15 and 20% carbohydrate. A food efficiency of 16.4 and 14.1% and,protein efficiency ratio of 0.41 and 0.34 obtained by fish fed on 15 and 20% carbohydrates in dietsrespectively were also superior to the other four groups. From this experiment 15 or 20% carbohydratesappeared optimal in the diets of C. batrachus fry.